2017
DOI: 10.1080/17470919.2017.1324521
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating methods of correcting for multiple comparisons implemented in SPM12 in social neuroscience fMRI studies: an example from moral psychology

Abstract: In fMRI research, the goal of correcting for multiple comparisons is to identify areas of activity that reflect true effects, and thus would be expected to replicate in future studies. Finding an appropriate balance between trying to minimize false positives (Type I error) while not being too stringent and omitting true effects (Type II error) can be challenging. Furthermore, the advantages and disadvantages of these types of errors may differ for different areas of study. In many areas of social neuroscience … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…Furthermore, based on findings from such future studies, guidelines for analysis for end users might also need to be revised and amended. Second, researchers have developed alternative methods for inference and thresholding, such as Statistical Non-parametric Mapping (SnPM; Nichols, 2012), Threshold-free Cluster Enhancement (TFCE; Smith and Nichols, 2009), and 3dClustSim with autocorrelation function (Cox et al, 2017); previous research has demonstrated that the application of the aforementioned methods can effectively address current issues on fMRI analysis, such as inflated false positives (Nichols and Holmes, 2002;Smith and Nichols, 2009;Eklund et al, 2016;Han and Glenn, 2017). However, because those methods are not available as basic functions in SPM 12, we did not test the alternative methods with Bayesian inference due to the limited scope of the present study, introducing Bayesian inference to end users who are familiar with SPM 12's default settings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on findings from such future studies, guidelines for analysis for end users might also need to be revised and amended. Second, researchers have developed alternative methods for inference and thresholding, such as Statistical Non-parametric Mapping (SnPM; Nichols, 2012), Threshold-free Cluster Enhancement (TFCE; Smith and Nichols, 2009), and 3dClustSim with autocorrelation function (Cox et al, 2017); previous research has demonstrated that the application of the aforementioned methods can effectively address current issues on fMRI analysis, such as inflated false positives (Nichols and Holmes, 2002;Smith and Nichols, 2009;Eklund et al, 2016;Han and Glenn, 2017). However, because those methods are not available as basic functions in SPM 12, we did not test the alternative methods with Bayesian inference due to the limited scope of the present study, introducing Bayesian inference to end users who are familiar with SPM 12's default settings.…”
Section: Discussionmentioning
confidence: 99%
“…where V ovl is the number of voxels showing significant activity in both images, and V meta and V synth are the number of voxels showing significant activity in the result of our meta-analysis and that from NeuroSynth, respectively (Han & Glenn, 2018). This overlap index was employed in the present study because it does take into account both false positive voxels, voxels reported to be active in the meta-analysis result image but are not in fact active in the standard image, and false negative voxels, voxels reported to be inactive in the meta-analysis image but are in fact active in the standard image.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Unfortunately, reports suggest that such may not be working well in practice. For example, an analysis by Han and Glenn’s (2017) shows Bonferroni correction and FDR are inappropriate for use because they are either too harsh or liberal in controlling for type I errors. Instead, they found that random field theory (RFT) familywise error correction (FWE)-applied voxel-wise thresholding struck a balance between the two methods, and they deemed it acceptable for fMRI data analysis in moral psychology.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers can easily compute it without much statistical and computational knowledge. BF has several advantages when compared to P -values, which we will discuss in the next section, particularly in the cases of studies with small, underpowered samples, which are prevalent in social and cognitive neuroscientific studies ( Han and Glenn, 2017 ).…”
Section: Introductionmentioning
confidence: 99%